Exploring the influence of company sport club involvement on employee outcomes - Paul Yuseung Doh; Chanwook Do; Minjung Kim (Journal of Applied Sports Management, 2024)
This study investigates the influence of company sport club involvement on employee outcomes, including cultural intelligence (CQ), organizational commitment, job satisfaction, and task performance. Drawing upon the theoretical frameworks of self-determination theory and spillover theory, the research examines how participation in company sport clubs enhances intrinsic motivation and promotes positive workplace attitudes and behaviors. Data were collected from 320 employees in Korea who were involved in various company sport clubs. Structural equation modeling analysis confirms significant positive relationships between company sport club involvement and CQ, organizational commitment, job satisfaction, and task performance. The findings underscore the significance of integrating company sport clubs into organizational culture to foster employee well-being and productivity. Human resource managers and organizational leaders can leverage these insights to enhance employee engagement and organizational performance. Keywords: company sport, organizational behavior, cultural intelligence, employee well-being
Keywords: company sport; organizational behavior; cultural intelligence; employee well-being